Variability in Phelan-McDermid Syndrome in a Cohort of 210 Individuals - Nevado, Julián; García-Miñaúr, Sixto; Palomares-Bralo, María; Vallespín, Elena; Guillén-Navarro, Encarna; Rosell, Jordi; Bel-Fenellós, Cristina; Mori, María Ángeles; Milá, Montserrat; Campo, Miguel del; Barrúz, Pilar; Santos-Simarro, Fernando; et al. (Frontiers in Genetics, 2022)
Phelan-McDermid syndrome (PMS, OMIM# 606232) results either from different rearrangements at the distal region of the long arm of chromosome 22 (22q13.3) or from pathogenic sequence variants in the SHANK3 gene. SHANK3 codes for a structural protein that plays a central role in the formation of the postsynaptic terminals and the maintenance of synaptic structures. Clinically, patients with PMS often present with global developmental delay, absent or severely delayed speech, neonatal hypotonia, minor dysmorphic features, and autism spectrum disorders (ASD), among other findings. Here, we describe a cohort of 210 patients with genetically confirmed PMS. We observed multiple variant types, including a significant number of small deletions (<0.5 Mb, 64/189) and SHANK3 sequence variants (21 cases). We also detected multiple types of rearrangements among microdeletion cases, including a significant number with post-zygotic mosaicism (9.0%, 17/189), ring chromosome 22 (10.6%, 20/189), unbalanced translocations (de novo or inherited, 6.4%), additional rearrangements at 22q13 (6.3%, 12/189), as well as other copy number variations in other chromosomes, unrelated to 22q deletions (14.8%, 28/189). We compared the clinical and genetic characteristics among patients with different sizes of deletions and with SHANK3 variants. Our findings suggest that SHANK3 plays an important role in this syndrome but is probably not uniquely responsible for all the spectrum features in PMS. We emphasize that only an adequate combination of different molecular and cytogenetic approaches allows an accurate genetic diagnosis in PMS patients. Thus, a diagnostic algorithm is proposed.